Print casebooks 10 the best in advertising - Rutter Kaye, Joyce (New York: RC Publications, 1994)
Contents: Here are 52 print ads, billboards, and tv commercials, encompassing come of the most effective end influential advertising compaigs of the last several years. here you'll find shrewdly conceived advertising not only for big national clients like RCH, porsche, lee jeans, time magazine, timex and jell-O, but dso for local clients like the edgar allan poe museum in richmand. the mythie theate company in new york, and the united way of metropolitan atlanta.
Keywords: Campaña Publicitaria; Publicidad - Propaganda